The causes of war. Volume IV, 1650-1800 - Gillespie, Alexander (Oxford : Hart Publishing, 2021)
"This is the fourth volume of a projected six-volume series charting the causes of war from 3000 BCE to the present day, written by a leading international lawyer, and using as its principal materials the documentary history of international law, largely in the form of treaties and the negotiations which led up to them. These volumes seek to show why millions of people, over thousands of years, slew each other. In departing from the various theories put forward by historians, anthropologists and psychologists, the author offers a different taxonomy of the causes of war, focusing on the broader settings of politics, religion, migrations and empire-building. These four contexts were dominant and often overlapping justifications during the first four thousand years of human civilisation, for which written records exist."--
I. Introduction -- 1. The Conversation on Sunday Afternoon -- 2. Utopia -- 3. Facts -- 4. Casus Belli in Practice -- 5. Volumes One to Three -- 6. Volume Four -- II. The Glorious Revolution -- 1. Introduction -- 2. Republics -- 3. The First War between the Dutch and English Republics -- 4. Allies with France, War with Spain -- 5. The Restoration -- 6. Alliance with Portugal and Further War with Spain -- 7. A Second War with the Dutch, and then the French -- 8. Alliance with France, Further War against the Dutch, and Another Peace -- 9. War and Peace with English and the Indigenous Communities in the Colonies -- 10. The Causes of the Revolution in England -- 11. The Invasion of England -- 12. The Glorious Revolution -- 13. John Locke -- 14. Constitutional Monarchy Entrenched -- 15. Liberty -- 16. Conclusion -- III. The Wars of Louis XIV -- 1. Introduction -- 2. The Ongoing Conflict with Spain -- 3. The War of Spanish Inheritance -- 4. The War of France and England against the Dutch Republic -- 5. The Reunion Wars -- 6. The Nine Years War -- 7. The War of Spanish Succession -- 8. Conclusion -- IV. The Interregnum -- 1. Introduction -- 2. Succession and Dynastic Considerations -- 3. The War of the Quadruple Alliance -- 4. The 1720s -- 5. Skirting a Major Conflict in the 1730s -- 6. Conclusion -- V. The War of Austrian Succession -- 1. Introduction -- 2. The Prize -- 3. Frederick II -- 4. The Opportunities for Others of the Habsburg Inheritance -- 5. Splintering the Opposition and Building New Alliances -- 6. The Slide Towards World War -- 7. Coming to the Boil -- 8. Full Boil -- 9. Bonnie Prince Charlie -- 10. Expansion and Exhaustion -- 11. The Treaty of Aix-la-Chapelle -- 12. Conclusion -- VI. The Seven Years War -- 1. Introduction -- 2. The New Plan -- 3. Trouble in the Colonies -- 4. Austria Backs Away from its Alliance with Britain -- 5. Britain Makes a Deal with Russia -- 6. The Treaty of Westminster Trumps that with Russia -- 7. Misreading the Opposition -- 8. New Friends and New Neutrals: The First Treaties of Versailles -- 9. The Deepening Conflict -- 10. The Invasion of Saxony -- 11. The Widening Conflict in India and North America -- 12. The Expansion of the Anti-Prussian Alliance -- 13. Extreme Pressure Applied on Prussia -- 14. The Push Back -- 15. A Good Year for Britain -- 16. The Pressure on Prussia and Victories for Britain -- 17. The Entry of Spain -- 18. The Exit of Russia -- 19. The Last Actions -- 20. The Peace of Paris -- 21. The Peace of Hubertusburg -- 22. Conclusion -- VII. The War of American Independence -- 1. Introduction -- 2. Before the Revolution -- 3. After the Seven Years War -- 4. Land and Native Americans -- 5. Sugar and Stamps -- 6. A Revised Approach -- 7. Tea -- 8. The Intolerable Acts -- 9. 1774: The Reaction -- 10. A Shot Heard Across the World -- 11. The Justification and Escalation -- 12. The First Help and Assistance -- 13. Common Sense -- 14. The Declaration of Independence -- 15. Military Survival and Political Cohesion -- 16. The French Enter the War -- 17. As the War Grinds on in North America, it Expands into Other Parts of the World -- 18. Spain Enters the Fray -- 19. Tupac's Rebellion in Peru -- 20. A Global War -- 21. The League of Armed Neutrality -- 22. The Last Years of the Conflict -- 23. Peace -- 24. The Native American Question -- 25. What the Americans Fought for -- 26. The United States and the Wider World in the 1790s -- 27. The French Revolution and the Turn Towards Isolationism -- 28. Conclusion -- VIII. The French Revolution -- 1. Introduction -- 2. Kings -- 3. Philosophers -- 4. The Fuse to Revolution in France -- 5. The Foreign Context -- 6. War -- 7. The First Coalition against the Republic of France -- 8. Internal Enemies -- 9. The War Changes, Turns and Expands -- 10. Britain Fights Alone -- 11. The Second Coalition -- 12. Napoleon -- 13. Conclusion -- IX. Slavery -- 1. Introduction -- 2. Numbers and Impact -- 3. Supply -- 4. Traders -- 5. Indentured Labour -- 6. The Laws of Slavery -- 7. Slave Revolts in the Second Half of the Seventeenth Century -- 8. Dissent against Slavery -- 9. Slave Revolts up to 1765 -- 10. The American Revolution -- 11. The Abolitionist Movement in Britain -- 12. The French Revolution -- 13. Saint Dominique/Haiti -- 14. The Revolt -- 15. Conclusion -- X. The Wars of North and Eastern Europe -- 1. Introduction -- 2. The First Northern War -- 3. The Second Northern War -- 4. Between the Wars -- 5. The War of Polish Succession -- 6. The Austrian War of Succession -- 7. The Seven Years War -- 8. Catherine the Great -- 9. The First Partition of Poland -- 10. Rebellions against Serfdom -- 11. The Almost War of Bavarian Succession -- 12. The Second Partition of Poland -- 13. The End of the Commonwealth of Poland-Lithuania -- 14. Paul I -- 15. Conclusion -- XI. Religion -- 1. Introduction -- 2. Enlightenment -- 3. Religion as a Pretext for War -- 4. The Movement Towards Tolerance -- 5. Religion in the Revolutionary Wars -- 6. Conclusion -- XII. The Muslim Territories -- 1. Introduction -- 2. The Ottoman Empire -- 3. The Siege of Vienna -- 4. North Africa -- 5. New Ottoman Conflict with Russia -- 6. New Ottoman Conflict with the Venetians and the Habsburgs -- 7. The End of the Safavid Dynasty -- 8. The Rise of Nader Shah -- 9. The Austro-Russian and Ottoman War of 1735 to 1739 -- 10. Aurangzeb and the Mughal Empire -- 11. Nader Shah at Full Strength -- 12. The Rise of the British in India -- 13. Three Decades of Russian-Ottoman Conflict -- 14. War and Peace in Eighteenth-century North Africa -- 15. The Challenge at the Epicentre of the Ottoman Empire -- 16. Conclusion -- XIII. China and its Neighbours -- 1. Introduction -- 2. The Shunzhi Emperor -- 3. The Kangxi Emperor -- 4. The Yongzheng Emperor -- 5. The Qianlong Emperor -- 6. Europeans -- 7. Conclusion -- XIV. Grand Plans for Peace -- 1. Introduction -- 2. Hobbes -- 3. Penn -- 4. Leibniz -- 5. The Abbé Charles de Saint-Pierre -- 6. Vattel and Wolff -- 7. Voltaire -- 8. Rousseau -- 9. Bentham -- 10. Kant -- 11. Conclusion -- XV. Conclusion -- 1. Absolute Rulers -- 2. Religion -- 3. Ideologies of the Enlightenment -- 4. The Muslim Territories -- 5. China and Asia.
Includes bibliographical references and index.
Previously issued in print: Hart Publishing, 2021.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: War -- Causes; War (International law) -- History; Military history, Ancient; Military history; International law; Electronic books